Exploring the impact of Visual Impairment Awareness Training: Phenomenographic Research with PGCE Secondary Art & Design Trainees - Dunn, Harriet (PRISM: Casting New Light on Learning, Theory and Practice, 2024)
Post Graduate Certificate of Education (PGCE) secondary art and design trainees participated in visual impairment awareness training (VIAT), prior to facilitating an art education project for visually impaired (VI) pupils. This was designed to better prepare them for working with a range of learners. A phenomenographic methodology and research approach was adopted – to capture key data relevant to learning, gaining knowledge and understanding in education settings. This contributed to knowledge in the field, highlighting the shift in trainees perspectives towards working with VI pupils, as a consequence of participation in VIAT. Existing literature recognises that VIAT provides an understanding of VI but cannot replicate everyday experiences. The findings as part of this study indicate that initially an empathy response was evoked, as trainees were apprehensive about working with VI pupils. Following VIAT, trainees gained a superficial overview of VI. Having gained experience, an advocacy response was evoked as trainees felt more comfortable asking pupils how their needs could be met.